Pengaruh Pendidikan, Output Sektor Pertanian, Dan Upah Pertanian Terhadap Penyerapan Tenaga Kerja Sektor Pertanian Di Indonesia - Annisa Maharani Putri; Ariusni (Universitas Negeri Padang, 2024)
The aim of this research is to analyze the influence of education, agricultural sector output, agricultural wages on employment in the agricultural sector in Indonesia from 2014 to 2022. Using secondary data sourced from the Central Statistics Agency (BPS). The dependent variable is Labor Absorption in the Agricultural Sector, and the independent variables consist of Education (Average years of schooling), Agricultural Sector Output (GDP in the Agricultural Sector), and Agricultural Wages. The analytical tool in this research uses panel data regression with the Fixed Effect model method, Cross Section consisting of 34 Provinces in Indonesia and a time series for 2014-2022. The findings of this research reveal that (1) The average level of years of schooling has a negative and significant influence on labor absorption in the agricultural sector in Indonesia. (2) GRDP in the agricultural sector has a positive and significant influence on labor absorption in the agricultural sector in Indonesia. (3) Agricultural wages have a negative and insignificant influence on labor absorption in the agricultural sector in Indonesia. and this research uses a panel data regression analysis tool using the Fixed Effect model method.